Koordinasi dalam Implementasi Kebijakan Pencegahan Stunting di Kota Padang - Febby Febrian; Rahmadani Yusran (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2021)
The study to analyze coordination about stunting prevention policies in Padang. The mechanisms coordination about stunting prevention policies at Padang. And factors inhibiting of stunting prevention coordination in the City of Padang. The research is a qualitative with descriptive analyze. The research was related agencies at Padang that are relevant to the implementation of stunting prevention policy coordination at Padang. This related agency are also the research informant. Got that information that the coordination of stunting prevention policy at Padang was only running at the sectoral level. The Health Office and its staff and have not coordinated cross-sectoral with other agencies that specifically discuss stunting prevention. The coordination mechanism in the implementation of stunting prevention policies at Padang has only been implemented in the ranks of the Health Office and its staff in the form of mini workshops involving the puskesmas team, sub-district officials and village staff through the nutrition program. The inhibiting factor in the implementation of coordination of stunting prevention policies at Padang was that absence regulations affects the clarity of the main functions and duties of the institutions involved, the absence of a special budget on stunting prevention. It’s caused to the perceived low incidence of stunting at Padang City and Padang City which are not included in the stunting locus area.